Interiority and Resilience - Atmodiwirjo, Paramita; Yatmo, Yandi Andri (Interiority, 2026)
The disciplines of interior architecture and interior design operate within a world characterised by constant changes. Projecting the future of the interior requires an understanding of how the discipline and practice can manoeuvre exquisitely within such complexities. It calls for design scholarship that promotes resilience as a key condition for responding to constant changes. The interior demonstrates resilience through its capacity to sustain culture, humanistic values, and local sociospatial practices, allowing it to navigate the dynamics of global flux. A call for interior resilience presents an opportunity for interior practices grounded in humanistic and cultural approaches to address uncertainties, instability, and alternative trajectories. This issue of Interiority highlights a series of inquiries and approaches to establish resilience through humanistic and cultural perspectives on interiority. They highlight the interior as a lived environment that manifests changes, sociocultural dynamics, and embodied experiences. They demonstrate the possibilities to produce interiority that promotes the built environment’s resilience, enhancing interior practice’s role toward social and cultural responsibility.